Interplanetary Shock Parameters Near Jupiter's Orbit. Issue 11 (10th June 2019) - Echer, E.
Abstract: Fast interplanetary shocks occurrence, their parameters, and drivers near Jupiter's orbit are determined in this paper. It was found that 70% of the fast shocks are forward (FS) and 30% are reverse (RS). Interplanetary coronal mass ejection‐driven FS occur more frequently in all solar cycle phases except in the declining phase, when corotating interaction region‐driven shocks predominate. Most of the shocks were quasi‐perpendicularly (65° to 70°) propagating relative to the ambient interplanetary magnetic field. The average shock magnetosonic Mach number is slightly higher for FS (2.6) than for RS (2.4), which in turn are stronger than shocks near 1 and 10 AU reported in previous works. This occurs because of the full development of corotating interaction region shocks and higher occurrence of strong interplanetary coronal mass ejections near 5 AU and that the magnetosonic speed at 5 AU has only 60% of its value at 1 AU. Plan Language Summary: Interplanetary shock waves are sudden variations in solar wind plasma and magnetic field parameters. They propagate in the interplanetary space and have important effects on planetary magnetospheres. For instance, shocks cause expansions and compressions of Jupiter's magnetosphere and trigger its auroral emissions. In this work plasma and magnetic field data from several spacecraft that crossed interplanetary space near Jupiter's orbit space are analyzed. A list of interplanetary shocks is compiled, and their parameters and drivers are determined. It was found that shocks at 5 AU have preferentially a quasi‐perpendicular propagation to the magnetic field direction and are on average stronger than shocks observed near Earth's orbit. Key Points: Interplanetary shock occurrence, parameters, and drivers near Jupiter's orbit are determined There are about 70% fast forward and 30% reverse shocks; about 90% of RS are CIR driven, while 45% of FS are CIR driven and 55% are ICME driven Shocks at 5 AU are mostly quasi‐perpendicularly propagating and stronger on average than shocks at 1 AU